Towards Macroscopic Crystalline 2D Polymers - Feng, Xinliang; Schlüter, A. Dieter (Angewandte Chemie International Edition, 2018)
Periodic and nanoporous monolayer polymers, the structures of which can be viewed as molecular fishing nets, have been classified as 2D polymers. They have been previously synthesized under mild photoirradiation conditions in the interior of layered single crystals of well‐designed monomers, followed by a liquid‐phase exfoliation. While these mild conditions allow for full structure control, the size of 2D polymers obtained cannot exceed that of the crystals from which they are prepared. In this Review, we discuss different concepts currently pursued to prepare macroscopically sized 2D polymers, focusing on syntheses at the air–water and liquid–liquid interfaces. While these interfaces are larger reaction loci than single crystals, sheet‐like polymers obtained at them pose complex and time‐consuming analytical challenges. Some of these challenges are concretely discussed and indicators are provided for identifying the promising cases, enabling to concentrate on them in the future research. Additionally, this Review discusses three representative examples of 2D polymers to provide a state‐of‐the‐art picture of this emerging field of polymer and materials science. Finally, we sketch the range of applications, such as nanomembranes, electronics, optoelectronics, and electrocatalysts for water splitting, that are relevant for these novel organic 2D materials. From single crystals to monolayers at the air–water interface is a current trend in the synthesis of 2D polymers. This Review explains the advantages and downsides faced when attempting to form 500 000 chemical bonds in a controlled fashion within a single polymer sheet. Recent cases are used to address structural, chemical, and analytical challenges associated with such an endeavor. The manifold applications expected for 2D polymers are the motivation to enter into this exciting field.